2018
DOI: 10.3390/molecules23020273
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Catalytic Activity of Nickel Molybdate (NiMoO4) Nanoparticles

Abstract: Nickel molybdate (NiMoO4) nanoparticles were synthesized via calcination of an oxalate complex in static air at 500 °C. The oxalate complex was analyzed by thermal gravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). The as-synthesized nickel molybdate was characterized by Brunauer–Emmett–Teller technique (BET), X-ray diffraction (XRD), and transmission electron microscopy (TEM) and its catalytic efficiency was tested in the reduction reaction of the three-nitrophenol isomers. The nic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Figure 2C shows the FTIR spectra of NiMoO 4 , Mn 0.1 Ni 0.9 MoO 4 , and Mn 0.1 Ni 0.9 MoO 4 /rGO, in which the stretching vibrations of Mo−O, Mo−O−Mo, and MoO are all detected. 20 It is interesting to notice that the absorption peaks of Mo−O and MoO in NiMoO 4 at 745 and 963 cm −1 red-shift to 736 and 959 cm −1 in Mn 0.1 Ni 0.9 MoO 4 /rGO, respectively. The red-shift may be attributed to the change of chemical environment after the Mn-doping, especially the change relating to the orbital hybridization of Mn atoms and host atoms of NiMoO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 2C shows the FTIR spectra of NiMoO 4 , Mn 0.1 Ni 0.9 MoO 4 , and Mn 0.1 Ni 0.9 MoO 4 /rGO, in which the stretching vibrations of Mo−O, Mo−O−Mo, and MoO are all detected. 20 It is interesting to notice that the absorption peaks of Mo−O and MoO in NiMoO 4 at 745 and 963 cm −1 red-shift to 736 and 959 cm −1 in Mn 0.1 Ni 0.9 MoO 4 /rGO, respectively. The red-shift may be attributed to the change of chemical environment after the Mn-doping, especially the change relating to the orbital hybridization of Mn atoms and host atoms of NiMoO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…FTIR and Raman spectroscopies were further used to explore the chemical composition and molecular structure of as-prepared samples. Figure C shows the FTIR spectra of NiMoO 4 , Mn 0.1 Ni 0.9 MoO 4 , and Mn 0.1 Ni 0.9 MoO 4 /rGO, in which the stretching vibrations of Mo–O, Mo–O–Mo, and MoO are all detected . It is interesting to notice that the absorption peaks of Mo–O and MoO in NiMoO 4 at 745 and 963 cm –1 red-shift to 736 and 959 cm –1 in Mn 0.1 Ni 0.9 MoO 4 /rGO, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Their catalytic activity enables different processes such as the selective oxidation of methanol or the reduction of nitrophenol isomers. Deng et al reported about a certain kind of molybdenum-containing high-entropy oxide with desulfurization capabilities. Apart from the catalytic properties, copper molybdate can be used as a photocatalyst, and iron molybdate exhibits interesting ferromagnetic properties at room temperature. , Furthermore, metal molybdates show promise for application in (super)­capacitors and batteries. Molybdates with “small” Mo numbers (e.g., MoO 4 2– , Mo 2 O 7 2– , etc.) are composed of Mo 6+ ions, tetrahedrally or octahedrally coordinated by oxygen ions (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, metal oxides as potential materials with different capabilities have been studied [21]. The family of metal molybdates is one of the most promising examples of the mixed metal oxides, which have been extensively studied in recent years [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%